The Efficacy of Reality Therapy-Based Group Counseling in Reducing Alexithymia among Adolescent Bullying Perpetrators - Intan Verly Syafitri; Yeni Karneli; Firman (Universitas Ahmad Dahlan, 2026)
Bullying remains a persistent problem in schools, and deficits in emotional processing may contribute to perpetration. Adolescents with high levels of alexithymia often have difficulty identifying and describing their emotions and interpreting others’ affective cues, which may undermine empathy and increase the risk of harmful interpersonal behavior. This study evaluated the effectiveness of reality therapy–based group counseling in reducing alexithymia among adolescent bullying perpetrators. Using a quasi-experimental pretest–posttest control group design, 18 students from a state vocational high school in Padang were recruited via purposive sampling and allocated to an experimental group (n = 9) or a control group (n = 9). Alexithymia was assessed using a Likert-type scale administered before and after the intervention. Within-group changes were analyzed using the Wilcoxon signed-rank test, and between-group differences were examined using the Mann–Whitney U test. The results showed a significant reduction in alexithymia in the experimental group following reality therapy–based group counseling (Z = −2.666, p = .008). In addition, posttest alexithymia scores differed significantly between the experimental and control groups (U = 1.500, p = .001), indicating that reality therapy–based group counseling was more effective than standard group counseling in reducing alexithymia among adolescent bullying perpetrators.